2022
DOI: 10.1007/s12311-022-01487-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Motor Sequence Learning and Execution Through Anodal Cerebellar Transcranial Electrical Stimulation

Abstract: Cerebellum (CB) and primary motor cortex (M1) have been associated with motor learning, with different putative roles. Modulation of task performance through application of transcranial direct current stimulation (TDCS) to brain structures provides causal evidence for their engagement in the task. Studies evaluating and comparing TDCS to these structures have provided conflicting results, however, likely due to varying paradigms and stimulation parameters. Here we applied TDCS to CB and M1 within the same expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Biperiden has a high affinity for the M1 receptor (Bolden et al, 1992), which is primarily located in the hippocampus and the cerebral cortex, but also in the cerebellum, striatum and thalamus (Levey, 1993). Neuroimaging, anatomical and lesion studies have identified a cortical-subcortical network underpinning procedural learning, engaging a frontalparietal network (Eliassen et al, 2001;Hardwick et al, 2013;Müller et al, 2002;Rivera-Urbina et al, 2022;Tzvi et al, 2016) and the motor cortex, cerebellum, basal ganglia and ventral intermediate nucleus of the thalamus (Hardwick et al, 2013;Roy et al, 2019;Terzic et al, 2022;Voegtle et al, 2022Voegtle et al, , 2023. The presence of M1 receptors in the network underpinning procedural learning suggests a potential impact of biperiden on motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Biperiden has a high affinity for the M1 receptor (Bolden et al, 1992), which is primarily located in the hippocampus and the cerebral cortex, but also in the cerebellum, striatum and thalamus (Levey, 1993). Neuroimaging, anatomical and lesion studies have identified a cortical-subcortical network underpinning procedural learning, engaging a frontalparietal network (Eliassen et al, 2001;Hardwick et al, 2013;Müller et al, 2002;Rivera-Urbina et al, 2022;Tzvi et al, 2016) and the motor cortex, cerebellum, basal ganglia and ventral intermediate nucleus of the thalamus (Hardwick et al, 2013;Roy et al, 2019;Terzic et al, 2022;Voegtle et al, 2022Voegtle et al, , 2023. The presence of M1 receptors in the network underpinning procedural learning suggests a potential impact of biperiden on motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…The serial reaction time task (SRTT) is a widely used task to measure human and animal learning in the field of behavioural and cognitive neuroscience (Abrahamse et al, 2010; Christie & Dalrymple‐Alford, 2004; Schwarting, 2009; Werheid et al, 2003). Despite the seminal paper of Robertson (2007), a vast number of publications refer to this task as a ‘motor learning task’ (e.g., Borragán et al, 2022; Geiger et al, 2018; Heyes & Foster, 2002; Hung et al, 2019; Kwon et al, 2010; Lum et al, 2022; Salehi et al, 2019; Sense & van Rijn, 2018; Voegtle et al, 2022). Just like Robertson (2007), 15 years later, here, we are still arguing that the SRTT is also a perceptual learning task, and we aim to shed light on the importance of avoiding the term ‘motor learning’ and referring to this task as a ‘visuomotor learning’ task.…”
Section: Introductionmentioning
confidence: 99%
“…Here we assessed the impact of biperiden on motor sequence learning and its neural correlates in healthy participants using a randomized, double-blind, placebo-controlled study design, employing the serial reaction time test (SRTT), a well-established approach to evaluation of motor sequence learning (Nissen & Bullemer, 1987;Terzic et al, 2022;Voegtle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Biperiden has a high affinity for the muscarinic M1 receptor (Bolden et al, 1992), which is primarily located in the hippocampus and the cerebral cortex, but also in the cerebellum, striatum, and thalamus (Levey, 1993). Neuroimaging, anatomical, and lesion studies have identified a cortical–subcortical network underpinning procedural learning, engaging a frontal–parietal network (Eliassen et al, 2001; Hardwick et al, 2013; Müller et al, 2002; Rivera-Urbina et al, 2022; Tzvi et al, 2016) and the motor cortex, cerebellum, basal ganglia, and ventral intermediate nucleus of the thalamus (Hardwick et al, 2013; Roy et al, 2019; Terzic et al, 2022; Voegtle et al, 2022; Voegtle et al, 2023). The presence of M1 receptors in the network underpinning procedural learning suggests a potential impact of biperiden on motor learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation